Impact of Haikal Hassan Endorsement on Repurchase Intention of Pizza Hut Muslim Consumers: Mediated by Religiosity - Syamsul Bahri; Juliana Nasution; Marliyah Marliyah (Research Synergy Foundation, 2024)
The controversy surrounding Haikal Hassan's endorsement of Pizza Hut products in Indonesia has sparked debates about the intersection of religious influence and consumer behaviour in the Muslim market, particularly following public concerns about the brand's perceived connection to Israel through its parent company's business relations. This situation raises questions about how religious figures' endorsements impact Muslim consumers' purchasing decisions, especially when promoting international food brands that face scrutiny over their global business affiliations. This research aims to quantitatively measure the effect of Haikal Hassan's endorsement on Muslim consumers' repurchase intention for Pizza Hut products, considering religiosity as an intermediary variable. Using a quantitative method with an explanatory design, this research involved 100 respondents of Pizza Hut Muslim consumers in Indonesia, which were determined using a purposive sampling approach. Information was obtained from a structured questionnaire and then examined using Path Analysis with SmartPLS version 4. According to the results, endorsement has a positive and significant effect on repurchase intention but a negative and significant effect on religiosity. On the other hand, religiosity has a negative and significant impact on repurchase intention and also significantly mediates the effect of endorsement on repurchase intention. These findings contribute to the understanding of Muslim consumer behaviour and the role of religiosity in marketing, and this can be a reference for companies in developing more appropriate marketing tactics that are sensitive to the religious values of Muslim consumers in Indonesia.